Rumor and Collective Action Frames: An Assessment of How Competing Conceptions of Gender, Culture, and Rule of Law Shaped Responses to Rumor and Violence in Afghanistan. (2nd January 2022) - Ibrahimi, Niamatullah
Abstract: How do rumors emerge and spread? One explanation emphasizes some form of crisis and uncertainty as the facilitating condition and another strand of research focuses on micro-level dynamics to explain how some groups are more vulnerable to rumors than others. This article applies framing theory to examine a rumor that led to violence that killed Farkhunda Malikzada in Afghanistan in March 2015 and three separate protests against the incident. Focusing on how different groups understand and reinterpret rumors, the article makes a distinction between rumor as an informational shortcut and an instrument of deliberate manipulation of information.